PELATIHAN MEDIA SOSIAL DALAM RANGKA MENGEMBANGKAN PANGSA PASAR DAN MENINGKATKAN OMZET PENGRAJIN BORDIR DAN KELOM GEULIS TASIKMALAYA - Santi Susanti; Fitri Perdana; Rachmaniar Rachmaniar (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This Community Service (PPM) is entitled "Social Media Training in Developing Market Share and Increasing Revenue of Embroidery and Kelom geulis Entrepreneurs". This activity is motivated by development of social media usage from communication media to a marketing media for products produced and sold by net citizens. This includes embroidery and kelom geulis entrepreneurs in Tasikmalaya city. However, not every entrepreneur uses social media as a marketing media for their products, especially middle-aged business owners. Even if using it, the management is not optimal, because of the limited human resources and the time they need to manage it. This PPM activity aims to foster enthusiasm for embroidery and kelom geulis entrepreneurs to optimize the use of social media as a marketing medium in order to expand the market and increase the revenue earned. Through the implementation of PPM, it is expected that embroidery and kelom geulis entrepreneurs can further optimize the use of social media as a marketing media for they products.